ANALYSIS OF THE THIRD QUARTER EXAMINATION IN FILIPINO 7 MATATAG CURRICULUM: BASIS FOR THE DEVELOPMENT OF A STANDARDIZED ASSESSMENT - OJEDA, GAY MARIE; ALTAYA, GRACELYN (International Journal of Arts, Sciences and Education, 2025)
ABSTRACT The exam is an important tool in education used to measure the knowledge and skills of students. In order to improve the quality of education, it is essential to analyze the exam to ensure its accuracy, fairness, and alignment with the goals of the curriculum. This study focuses on the validity analysis of the Filipino 7 exam for the Third Quarter as a basis for developing a standardized exam in a division in South Cotabato for the academic year 2024-2025. It used a quantitative research design, specifically the t-test validity, to assess the exam’s validity. Through purposive sampling, 220 respondents were selected for the initial exam evaluation, while 49 underwent the pretest and post-test. The analysis showed that the exam had high quality, balance, and a well-structured format, with proper distribution of difficulty levels and discrimination of the questions. The results also indicated high validity and reliability, confirming its credibility as an effective tool in assessing the knowledge and skills of students. Changes based on expert recommendations further improved the quality of the exam. Despite the uneven distribution of some topics, it proved effective in assessing key skills in Filipino. Overall, it has the potential to become a standardized assessment that will contribute to more accurate and fair evaluation of students.